Perlindungan Hukum Bagi Korban Pemerkosaan Pelaku Abortus Provokatus Di Tinjau Dari Undang-Undang Nomor 36 Tahun 2009 Tentang Kesehatan - Pratiwi, Ria; Saimima, Ika Dewi Sartika; Atmoko*, Dwi (Universitas Syiah Kuala, 2023)
Cases of sexual violence against women are still a serious threat in Indonesia. Rape victims take a long time to overcome the traumatic experience, and some never return to normal as before. A further impact as a result of sexual rape is that it causes rape victims to experience unwanted pregnancies. Those pregnancies that lead to rape victims have abortions or abortion provocatus. This study aims to find out how legal protection is for rape victims who commit abortions and to analyze how long the health law should allow for an abortion according to medical criteria. This study uses normative legal research methods. This study concludes that the Health Law regarding abortion is a realistic rule based on health aspects. It's just that it is necessary to reconstruct the article on abortion regulations related to rape. Provisions which allow abortion if the gestational age is 6 (six) weeks or 40 (forty) days. Age is calculated from the first day of the last menstruation. This research uses a normative juridical method supported by the reality that exists in today's society, so that the results of this research are expected to make a positive contribution in the field of law, especially for victims of rape in order to get the justice they should.